Kulturpolitikkens rolle i forskningen på Dramaturgi - Ejgod Hansen, Louise (Peripeti, 2020)
In this article, the author explores how and why cultural policy seems to be a strong element in the research at Dramaturgy at Aarhus University. Through analysis of key research publications as well as research interviews with the current members of staff at Dramaturgy (May 2019), she presents three different models for the way in which cultural policy is an element in the research at Dramaturgy: The layer cake, the pillar and the target. In addition, she discusses whether the mediality of theatre is part of the reason why cultural policy is a part of the research field of Dramaturgy more broadly.